Effect of visual cues and outcome feedback on physics problem solving in an online system - Weliweriya Liyanage, Nandana (Kansas State University, 2015)
With the progressive development of the educational technology, online learning systems are becoming a prominent feature in education today. We conducted a study to explore the effects of visual cues and outcome feedback on learning experience of students in an online environment. Our study was a follow up study to a previous research, which demonstrated the effectiveness of visual cues and feedback to improve physics problem solving. The participants (N=164) were enrolled in an algebra-based introductory level physics course at a U.S. Midwestern University. Participants completed a sequence of conceptual physics problems in an online environment. The study used a between subjects 2×2 quasi experimental design. Two groups of participants received visual cues and two did not receive cues. Two of the groups of participants received outcome feedback and two did not receive feedback. The effect of visual cues, feedback and their combination on the correctness of students’ responses to the online questions was analyzed. Implications of the study for online learning systems are discussed.
Keywords: Effect of visual cues and outcome feedback; Physics problem solving in an online system; Visual cues and outcome feedback; Visual cues; Outcome feedback; Physics problem solving; Educational Psychology (0525); Educational Tests and Measurements (0288); Physics (0605)